2020
DOI: 10.1186/s42238-020-00041-1
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of internet information sources on medical cannabis

Abstract: Background Medical cannabis users report that their knowledge regarding cannabis is predominantly from their own personal experiences and the Internet. Objective We summarize and describe information found through Internet searches on medical cannabis in English language websites. Methods We used terms related to medical cannabis in the Google search engine between Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…Local jargons such as “ntampi,” “abonsam tawa” (which means devil’s tobacco), and “wee Ghana” were also searched on Google and Google Scholar. The search method is similar to that of Kruger et al ( 2020 ) and Zembroski ( 2011 ). The search terms on Google were to identify general information from non-academic publications, blogs, news articles to academic publications, and books about cannabis.…”
Section: Methodsmentioning
confidence: 99%
“…Local jargons such as “ntampi,” “abonsam tawa” (which means devil’s tobacco), and “wee Ghana” were also searched on Google and Google Scholar. The search method is similar to that of Kruger et al ( 2020 ) and Zembroski ( 2011 ). The search terms on Google were to identify general information from non-academic publications, blogs, news articles to academic publications, and books about cannabis.…”
Section: Methodsmentioning
confidence: 99%
“…A 2017 survey has shown that 38.5% of US adults have searched for health information online (Finney Rutten et al, 2019 ), and the quality of the information available has been an active area of research. It is therefore expected that, with the development of medicinal products based on cannabis and their legalization in many countries, many patients will look online for information on their efficacy and availability (Kruger et al, 2020 ; Kruger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have analyzed the information available online on medical cannabis in general (Kruger et al, 2020 ) or for specific indications such as glaucoma. (Jia et al, 2021 ) A study by Jia et al found that 24% of the webpages returned by Google (and 59% of YouTube videos) had a positive stance on the use of medical cannabis in glaucoma (Jia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the largest cannabis market in the world, California (26), to test the hypothesis that higher THC content in cannabis dispensary products is positively correlated with higher prices, and that this correlation is not altered by major product attributes. We focus on the online market because online advertising is a major marketing strategy for cannabis (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%